Zeolite-assisted electrocoagulation for remediation of phosphate from calcium-phosphate solution. Issue 1 (July 2020) - Alenezi, Ahmad K.; Hasan, Hussein A.; Hashim, Khalid S.; Amoako-Attah, Joseph; Gkantou, Michaela; Muradov, Magomed; Kot, Patryk; Abdulhadi, Bareq
Abstract: Phosphorus is crucial to the growth of the skeletons and the living cell. However, elevated phosphate concentrations represent a problem due to its grave impacts on human health, animal and also because of its effects on water quality and economy. This research studies the applicability of filtration-electrocoagulation (filtration - EC) system to remove phosphate from wastewater when calcium is present as competitor ions. In laboratory batch trials, the ability of zeolite filter-electrocoagulation system to eliminate phosphate from artificial wastewater samples, in the presence of calcium as competitor ions, was tested. The research was initiated by studying the ability of the electrocoagulation method (EC), as a separated treatment unit, to remove phosphate from solutions that containing calcium ions. In this phase of the study, the influence initial pH, current densities and electrolysing period. Then, the new method, filtration-EC, was applied to treat solutions (with identical chemical composition to that used in the first phase) considering the effects of the initial pH, current densities, contact periods (in the filter), electrolysing period (in the EC cell) and zeolite dosage. The results of this research evidenced that the filtration - EC system completely removes phosphate from calcium-phosphate solution at pH, current density, dosage of zeolites, contact period and electrolysing period of 7, 2.0 mA.cm −2, 150.0 g, 30.0 minutes and 20.0 minutes, respectively.